Actualization of Indonesian Language and Culture for Teachers at San Fabian Elementary School Philippines - Ida Yeni Rahmawati; Betty Yulia Wulansari; Nurtina Irsad Rusdiana; Ayu Pujiati; Rizqia Putri Aziza; Siti Khoirul Bariyah; Febie Blas (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2024)
Acculturation of Indonesian culture and language into Filipino education is a crucial step in expanding cross-cultural awareness and strengthening international relations between the two countries. By introducing Indonesian culture and language to Filipino educators, it can enhance cultural ties between both nations. This research aims to actualize Indonesian language and culture among educators at San Fabian Elementary School. The study employs a descriptive qualitative research approach, with data sources consisting of 10 teachers from San Fabian Elementary School. Data collection techniques include a combination of observation and documentation. Data analysis follows Miles Huberman's approach, involving data collection, data reduction, data display, and conclusion drawing. Data validity is ensured through triangulation techniques.The findings of this research indicate that the acculturation of Indonesian language and culture into the Philippines can strengthen international relations through understanding and appreciation of each other's cultures and languages. The approach taken at San Fabian Elementary School could serve as a concrete step in building a strong foundation for cross-border educational collaboration, which in turn can contribute to broader peace and international cooperation.   Akumulasi budaya dan bahasa Indonesia ke dalam pendidik Filipina merupakan langkah penting dalam memperluas kesadaran lintas budaya dan memperkuat hubungan internasional kedua negara. Dengan mengenalkan budaya dan bahasa Indonesia kepada para pendidik Filipina dapat mempererat ikatan budaya kedua bangsa. Penelitian ini bertujuan untuk mengaktualisasikan bahasa dan budaya Indonesia di kalangan pendidik di SD San Fabian. Penelitian ini menggunakan pendekatan penelitian kualitatif deskriptif. Sumber datanya adalah para pendidik di SD San Fabian yang berjumlah 10 orang guru. Teknik pengumpulan data meliputi kombinasi observasi, dan dokumentasi. Teknik analisis data yang digunakan yaitu menggunakan Miles Huberman yang meliputi pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Keabsahan data dalam penelitian ini menggunakan teknik triangulasi data. Temuan penelitian ini menunjukkan bahwa akumulasi bahasa dan budaya Indonesia ke Filipina dapat memperkuat hubungan antarbangsa melalui pemahaman dan penghargaan terhadap budaya dan bahasa masing-masing. Pendekatan yang akan dilakukan di Sekolah Dasar San Fabian dapat menjadi langkah konkrit dalam membangun fondasi yang kokoh untuk kolaborasi pendidikan lintas batas, yang pada gilirannya dapat berkontribusi pada perdamaian dan kerja sama internasional secara lebih luas.